2011
DOI: 10.1007/s11604-010-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion magnetic resonance imaging with gadofosveset trisodium as a negative contrast agent for lymph node metastases assessment

Abstract: The SI of metastatic LNs at DWI is less suppressed than that of nonmetastatic LNs after the intravenous administration of gadofosveset trisodium. Therefore, intravenously administered gadofosveset trisodium shows promise for use as a negative contrast agent for discriminating metastatic from nonmetastatic LNs at DWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Within this period, MR imaging has undergone a massive technologic evolution, with faster imaging sequences and cardiac and respiratory triggering, enabling good correlation with cytologic and/or histologic findings at a higher spatial and temporal resolution (64,83). To investigate the relationship of additional technologic progress within this period on the overall pooled estimates (Ablavar; Lantheus Medical Imaging, North Billerica, Mass), may hold additional benefits to further improve the diagnostic performance of MR imaging (79)(80)(81). Additionally, MR imaging does not expose patients and medical personnel to irradiation, is less invasive, and is less expensive than FDG PET/ CT (82).…”
Section: Evidence-based Practice: Meta-analysis Of Mr Imaging For Nodmentioning
confidence: 99%
“…Within this period, MR imaging has undergone a massive technologic evolution, with faster imaging sequences and cardiac and respiratory triggering, enabling good correlation with cytologic and/or histologic findings at a higher spatial and temporal resolution (64,83). To investigate the relationship of additional technologic progress within this period on the overall pooled estimates (Ablavar; Lantheus Medical Imaging, North Billerica, Mass), may hold additional benefits to further improve the diagnostic performance of MR imaging (79)(80)(81). Additionally, MR imaging does not expose patients and medical personnel to irradiation, is less invasive, and is less expensive than FDG PET/ CT (82).…”
Section: Evidence-based Practice: Meta-analysis Of Mr Imaging For Nodmentioning
confidence: 99%
“…Preliminary studies have shown promise for the use of DWI to detect metastatic disease in lymph nodes 96,97 . To date there is only one published study evaluating its ability to evaluate axillary lymph nodes in patients with newly diagnosed breast cancer, which reported ADC values were significantly lower in metastatic versus benign axillary nodes 98 .…”
Section: Potential Clinical Applicationsmentioning
confidence: 99%
“…Vasovist R , a whole-body MRI image agent has been developed using Gd-albumin complex for detecting malignant lesions in humans. 65,66 Fluorescent imaging is another promising tool for cancer diagnosis. A nanocolloidal albumin-IRDye 800CW, with the size between 10-20 nm, has been synthesized by chemically conjugating fluorescent dye IRDye 800CW onto albumin.…”
Section: Biopolymermentioning
confidence: 99%